2020
DOI: 10.3892/mmr.2020.11274
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase and telomeres in aging theory and chronographic aging theory (Review)

Abstract: The current review focuses on the connection of telomerase and telomeres with aging. in this review, we describe the changes in telomerase and telomere length (Tel) during development, their role in carcinogenesis processes, and the consequences of reduced telomerase activity. More specifically, the connection of Tel in peripheral blood cells with the development of aging-associated diseases is discussed. The review provides systematic data on the role of telomerase in mitochondria, the biology of telomeres in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 191 publications
1
47
0
1
Order By: Relevance
“…Regular dividing cells and their progenitors, like lymphocytes, are strongly affected by telomerase activity and telomere shortening, affecting their potential for differentiation potential (Hodes et al, 2002). Recent publications showed that cellular ageing and immune proliferation have distinct effects on telomere length (Fali et al, 2019), with CD4 T cells stronger affected by ageing (Patrick et al, 2019) [reviewed in (Razgonova et al, 2020)]. We suggest that telomere length in leucocytes is likely determined by repeated immune activation, with overall 'healthy' lifestyles preserving telomere length.…”
Section: Common Featuresmentioning
confidence: 84%
“…Regular dividing cells and their progenitors, like lymphocytes, are strongly affected by telomerase activity and telomere shortening, affecting their potential for differentiation potential (Hodes et al, 2002). Recent publications showed that cellular ageing and immune proliferation have distinct effects on telomere length (Fali et al, 2019), with CD4 T cells stronger affected by ageing (Patrick et al, 2019) [reviewed in (Razgonova et al, 2020)]. We suggest that telomere length in leucocytes is likely determined by repeated immune activation, with overall 'healthy' lifestyles preserving telomere length.…”
Section: Common Featuresmentioning
confidence: 84%
“… 74 The activity of this enzyme represents a marker of cellular aging 75 and is implicated in aging-associated diseases. 76 However, compared to telomere length, telomerase function seems to correlate more faithfully with stress-related psychological mechanisms. 75 Stress leads to a decrease in its activity 77 while relaxation favors its functioning, 78 as our results appear to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase, the regulating enzyme of telomeres’ length, is an enzymatic complex consisting of two subunits, the catalytic subunit, the human telomerase reverse transcriptase (hTERT), and a template, the telomerase RNA component (TERC). Notwithstanding that, the telomeres’ length is induced in each cell cycle in a lower rate, endorsing cellular senescence ( 14 ). In non-cancerous somatic cells, TA is undetectable or present at low levels.…”
Section: Introductionmentioning
confidence: 99%